2021
DOI: 10.1016/j.chembiol.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Development and pre-clinical testing of a novel hypoxia-activated KDAC inhibitor

Abstract: Summary Tumor hypoxia is associated with therapy resistance and poor patient prognosis. Hypoxia-activated prodrugs, designed to selectively target hypoxic cells while sparing normal tissue, represent a promising treatment strategy. We report the pre-clinical efficacy of 1-methyl-2-nitroimidazole panobinostat (NI-Pano, CH-03), a novel bioreductive version of the clinically used lysine deacetylase inhibitor, panobinostat. NI-Pano was stable in normoxic (21% O 2 ) conditions and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 78 publications
(125 reference statements)
1
35
0
Order By: Relevance
“…In response to hypoxia, cancer cells may activate numerous hypoxia-inducible genes and thus promote angiogenesis to enhance proliferation. Hence, tumor hypoxia is usually associated with poor patient prognosis [48]. For example, previous studies have shown a link between hypoxia and CA19-9 that is a poor prognostic marker in cancers [49].…”
Section: Hypoxia and Ros In Tumor Progressionmentioning
confidence: 99%
“…In response to hypoxia, cancer cells may activate numerous hypoxia-inducible genes and thus promote angiogenesis to enhance proliferation. Hence, tumor hypoxia is usually associated with poor patient prognosis [48]. For example, previous studies have shown a link between hypoxia and CA19-9 that is a poor prognostic marker in cancers [49].…”
Section: Hypoxia and Ros In Tumor Progressionmentioning
confidence: 99%
“…This modification can prevent the interaction between the compound and the active site Zn 2 + ion, leading to an inactive compound. [12,30] Therefore, we adopted this approach to develop light-activated derivatives of Pano and selected the 4,5-dimethoxy-2-nitrobenzyl group as the photo-labile component (Scheme 1). [31][32][33]36,37] In addition, we also employed two negative control compounds a 4nitrobenzyl analogue (NB, 13) and an unsubstituted benzyl analogue (Bn, 14), which should not photorelease Pano.…”
Section: Chemistrymentioning
confidence: 99%
“…The synthesis of Pano was carried out as has been previously published. [12,38] The photolabile DMNB derivative of Pano (Zap-Pano, 1) and both control compounds were synthesised from the substituted hydroxylamines using a route previously developed within the group (Scheme 1). [12,30] Briefly, the nitrobenzyl halides (3 and 6) were reacted with Nhydroxyphthalimide, before deprotection with hydrazine, to give the substituted hydroxylamines (5 and 8).…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations